A Legacy of Innovation : Governors and Public Policy - Sribnick, Ethan G. (Book collections on Project MUSE., 2008)
Top scholars examine the changing role of state governors over the course of the twentieth century. This volume of essays tracks the evolution of gubernatorial leadership as it has dealt with critical issues, including conservation, transportation, civil rights, education, globalization, and health care.